2013
DOI: 10.1016/j.vaccine.2013.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Protection against avian necrotic enteritis after immunisation with NetB genetic or formaldehyde toxoids

Abstract: HighlightsNetB from Clostridium perfringens is the major virulence factor in avian necrotic enteritis.Vaccination with a NetB genetic or formaldehyde toxoid protects chicken in an in vivo disease model.NetB toxoids could form the bases of an efficient vaccine against necrotic enteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…The subclinical form of C. perfringens associated- NE can adversely affects growth rate, feed conversion, and flock uniformity ( Lovland and Kaldhusdal, 2001 ) resulting in serious economic losses on the poultry industry ( Timbermont et al, 2011 ). In addition to the etiological agent C. perfringens , predisposing factors such as Eimeria -induced mucosal damage and diets containing high levels of proteins are required to elicit the clinical signs and lesions of NE in poultry ( Fernandes da Costa et al, 2013 ). Those predisposing factors are hypothesized to change the gastrointestinal microbiota, providing a disrupted intestinal ecosystem in which C. perfringens can proliferate and cause disease ( Wu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The subclinical form of C. perfringens associated- NE can adversely affects growth rate, feed conversion, and flock uniformity ( Lovland and Kaldhusdal, 2001 ) resulting in serious economic losses on the poultry industry ( Timbermont et al, 2011 ). In addition to the etiological agent C. perfringens , predisposing factors such as Eimeria -induced mucosal damage and diets containing high levels of proteins are required to elicit the clinical signs and lesions of NE in poultry ( Fernandes da Costa et al, 2013 ). Those predisposing factors are hypothesized to change the gastrointestinal microbiota, providing a disrupted intestinal ecosystem in which C. perfringens can proliferate and cause disease ( Wu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have shown that chickens could be protected against C. perfringens -induced NE by injection with inactive and active toxins (Kulkarni et al, 2007 ; Jang et al, 2012 ) and antigenic proteins (Jiang et al, 2009 ). Since the discovery of its role in NE, the NetB toxin has been intensively studied with regards to vaccination, with some promising results (Fernandes da Costa et al, 2013 ; Keyburn et al, 2013a , b ).…”
Section: Vaccination Against C Perfringensmentioning
confidence: 99%
“…The protective effects of Se did not consistently increase proportionally with the increased dose of supplemented Se between 0.25 and 1.00 mg/ kg possibly because the highest dose may be influenced by toxic effects in this particular broiler group. C. perfringens α-toxin and NetB toxin are major virulence factors implicated in the pathogenesis of NE and are considered to be potential vaccine candidates in chickens (Fernandes da Costa et al, 2013;Jang et al, 2012;Sumners et al, 2012). The antibody levels against α-toxin and NetB toxin may be relevant in protective host immunity against C. perfringens .…”
Section: Body Weight Gain/bird(g)mentioning
confidence: 99%